Improving Voice Outcomes after Thyroid Surgery and Ultrasound-Guided Ablation Procedures - Pace-Asciak, Pia; Russell, Jon O.; Tufano, Ralph P. (Frontiers in Surgery, 2022)
Abstract The field of endocrine surgery has expanded from the traditional open neck approach to include remote access techniques as well as minimally invasive approaches for benign and malignant thyroid nodules. In experienced hands and with careful patient selection, each approach is considered safe, however complications can and do exist. Post-operative dysphonia can have serious consequences to the patient by affecting quality of life and ability to function at work and in daily life. Given the significance of post-procedural dysphonia, we review the surgical and non-surgical techniques for minimizing and treating recurrent laryngeal nerve injury that can be utilized with the traditional open neck approach, remote access thyroidectomy, or minimally invasive thermal ablation. Keywords: Thyroid surgery, Ultrasound-guided Ablation, Dysphonia, Voice, Vocal cord dysfunction